Sustainable Landscape Construction: Materials and Products — Aggregates and Precast Pavers and Blocks - Gail Hansen (EDIS)
ENH1147, a 1-page fact sheet by Gail Hansen, describes environmental issues, design strategies, and construction techniques for using aggregates and precast pavers and blocks in landscape construction. Includes references. Published by the UF Department of Environmental Horticulture, October 2009.